2017
DOI: 10.5194/amt-10-5089-2017
|View full text |Cite
|
Sign up to set email alerts
|

An aircraft gas chromatograph–mass spectrometer System for Organic Fast Identification Analysis (SOFIA): design, performance and a case study of Asian monsoon pollution outflow

Abstract: Abstract. Volatile organic compounds (VOCs) are important for global air quality and oxidation processes in the troposphere. In addition to ground-based measurements, the chemical evolution of such species during transport can be studied by performing in situ airborne measurements. Generally, aircraft instrumentation needs to be sensitive, robust and sample at higher frequency than ground-based systems while their construction must comply with rigorous mechanical and electrical safety standards. Here, we prese… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 71 publications
0
23
0
Order By: Relevance
“…Bangladesh, which are more polluted, convection transports the pollutants to the upper troposphere. At the same time, the strength of the convection changes within the monsoon due to differences in thermal heating between the relatively cold ocean and the hot land (Dethof et al, 1999).…”
Section: Ama Modesmentioning
confidence: 99%
See 1 more Smart Citation
“…Bangladesh, which are more polluted, convection transports the pollutants to the upper troposphere. At the same time, the strength of the convection changes within the monsoon due to differences in thermal heating between the relatively cold ocean and the hot land (Dethof et al, 1999).…”
Section: Ama Modesmentioning
confidence: 99%
“…For example, the in-service airborne projects CARIBIC (Civil Aircraft for the Regular Investigation of the atmosphere Based on an Instrument Container; e.g. Schuck et al, 2012;Rauthe-Schöch et al, 2016) and IAGOS-MOZAIC (IAGOS -In-service Aircraft for a Global Observing System) and MOZAIC (Measurements of OZone by Airbus In-service aircraft); Dethof et al, 1999;Barret et al, 2016) reported trace gas measurements in the Asian monsoon region. In addition, aircraft campaigns investigated the Asian monsoon during the MINOS campaign (Lelieveld et al, 2002;Scheeren et al, 2003), the Earth System Model Validation (ESMVal) campaign (Gottschaldt et al, 2017), and the Transport and Composition in the Upper Troposphere and Lowermost Stratosphere (TACTS) campaign (Vogel et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although canister air sampling typically generates data at a much lower spatial coverage, the postflight analysis allows a wider range of substances to be measured. Thus, air sample collection is a well-established part of the scientific payload of both campaign-type studies such as the HIPPO (Wofsy, 2011) and ATTREX (Navarro et al, 2015;Jensen et al, 2017) projects and long-term projects such as CONTRAIL (Machida et al, 2008) and IAGOS-CARIBIC (Brenninkmeijer et al, 2007;Petzold et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The Civil Aircraft for the Regular Investigation of the atmosphere Based on an Instrument Container (CARIBIC) project (http://www.caribic-atmospheric.com/, last access date: 27 June 2019) investigates atmospheric composition from aboard a Lufthansa passenger aircraft equipped with a sophisticated air inlet system (Brenninkmeijer et al, 2007). CARIBIC is a long-term scientific project, employing a comprehensive set of instruments for performing simultaneous measurements of trace gases and aerosol particles inside a 1.5 t airfreight container during regular long-distance flights of the aircraft.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation